Influence of Er:YAG laser on surface treatment of aged composite resin to repair restoration - Rossato, D. M. [UNESP]; Bandeca, Matheus Coelho [UNESP]; Saade, E. G. [UNESP]; Lizarelli, R. F. Z.; Bagnato, V. S.; Saad, José Roberto Cury [UNESP] (Maik Nauka/interperiodica/springer, 2009)
The purpose of this study was to investigate the effect of Er:YAG laser on surface treatment to the bond strength of repaired composite resin after aged. Sixty specimens (n = 10) were made with composite resin (Z250, 3M) and thermocycled with 500 cycles, oscillating between 5 to 55A degrees C. The specimens were randomly separated in six groups which suffered the following superficial treatments: no treatment (GI, control), wearing with diamond bur (GII), sandblasted with aluminum oxide with 27.5 A mu m particles (GIII) for 10 s, 200 mJ Er:YAG laser (GIV), 300 mJ Er:YAG laser (GV), and 400 mJ Er:YAG laser (GVI), with the last 3 groups under a 10 Hz frequency for 10 s. Restoration repair was done using the same composite. The shear test was done into the Universal testing machine MTS-810. Analyzing the results through ANOVA and Tukey test, no significant differences were found (p-value is 0.5120). Average values analysis showed that superficial treatment with aluminum oxide presented the highest resistance to shear repair interface (8.91MPa) while 400 mJ Er:YAG laser presented the lowest (6.76 MPa). Fracture types analysis revealed that 90% suffered cohesive fractures to GIII. The Er:YAG laser used as superficial treatment of the aged composite resin before the repair showed similar results when used diamond bur and sandblasting with aluminum oxide particles.